2022
DOI: 10.1093/braincomms/fcac248
|View full text |Cite
|
Sign up to set email alerts
|

Mutant huntingtin messenger RNA forms neuronal nuclear clusters in rodent and human brains

Abstract: Mutant mRNA and protein contribute to the clinical manifestation of many repeat-associated neurological disorders, with the presence of nuclear RNA clusters being a common pathological feature. Yet, investigations into Huntington's disease – caused by a CAG repeat expansion in exon 1 of the huntingtin (HTT) gene – have primarily focused on toxic protein gain-of-function as the primary disease-causing feature. To date, mutant HTT mRNA has not been identified as an in vivo hallmark of Huntington’s disease. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 87 publications
3
10
0
Order By: Relevance
“…The exact role of mutant transcripts in pathogenic mechanisms in polyQ diseases is being unraveled [10][11][12][13]. RNA-related studies have demonstrated so far: incomplete splicing of HTT mRNA [14], abnormal interactions of RNAs containing expanded CAG repeats with proteins [15,16], and RNA foci formation [17,18], and potential importance of alternative polyadenylation of various polyQ transcripts [19]. Furthermore, mutant polyQ disease transcripts have been shown to be promising therapeutic targets in strategies that aim to downregulate mutant gene expression [2,9,20].…”
Section: Introductionmentioning
confidence: 99%
“…The exact role of mutant transcripts in pathogenic mechanisms in polyQ diseases is being unraveled [10][11][12][13]. RNA-related studies have demonstrated so far: incomplete splicing of HTT mRNA [14], abnormal interactions of RNAs containing expanded CAG repeats with proteins [15,16], and RNA foci formation [17,18], and potential importance of alternative polyadenylation of various polyQ transcripts [19]. Furthermore, mutant polyQ disease transcripts have been shown to be promising therapeutic targets in strategies that aim to downregulate mutant gene expression [2,9,20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we detected the m6A methylation in polyadenylated Htt1a mRNAs, indicating its persistence during RNA maturation and potential roles in Htt1a mRNA fate. For instance, it has been shown that Htt1a can be found in the nucleus in the form of RNA foci in YAC128 mice 7 and in HD post-mortem brains which are likely caused by somatic expansion of the CAG repeats 8 . Although the direct function of m6A modifications in partitioning mRNAs into stress granules in vivo is unclear, it has been suggested that m6A, particularly in longer mRNAs containing multiple numbers of heavily modified m6A sites, can be involved in stress granule recruitment 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the observed effect in our experiment could be driven by a reduction in the production of the toxic 90 aa N-terminal HTT-exon1 protein as a consequence of the downregulation of Htt1a transcripts. However, in line with the potential role of Htt1 a in disease progression by formation of RNA foci at transcriptional sites 8 , it is also possible that reduced methylation in Htt1a would reduce the interaction with other Htt transcripts in RNA clusters avoiding for instance, sequestering of RNA binding proteins involved in DNA damage 80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that uninterrupted CAG repeat length, not polyQ length (encoded by CAA-CAG), affects the rate of pathogenesis in HD patients, suggesting the potential importance of mutant HTT DNA / mRNA in HD ( 4 ). Indeed, in mouse models of HD, introducing a copy of huntingtin containing the mutant expanded CAG tract leads to HD-like phenotypes in vivo ( 5 7 ). The ability of different compounds to modulate not only the protein but also mutant HTT mRNA needs to be considered.…”
Section: Introductionmentioning
confidence: 99%